Fabrication of nano-mosquitocides using chitosan from crab shells: impact on non-target organisms in the aquatic environment - Murugan, Kadarkarai; Jaganathan, Anitha; Dinesh, Devakumar; Suresh, Udaiyan; Rajaganesh, Rajapandian; Chandramohan, Balamurugan; Subramaniam, Jayapal; Paulpandi, Manickam; Vadivalagan, Chitravel; Amuthavalli, Pandiyan; Wang, Lan; Hwang, Jiang Shiou; et al. (Elsevier, 2016)
Mosquitoes are arthropods of huge medical and veterinary relevance, since they vector pathogens and parasites of public health importance, including malaria, dengue and Zika virus. Currently, nanotechnology is considered a potential eco-friendly approach in mosquito control research. We proposed a novel method of biofabrication of silver nanoparticles (AgNP) using chitosan (Ch) from crab shells. Ch-AgNP nanocomposite was characterized by UV–vis spectroscopy, FTIR, SEM, EDX and XRD. Ch-AgNP were tested against larvae and pupae of the malaria vector Anopheles stephensi obtaining LC50 ranging from 3.18 ppm (I) to 6.54 ppm (pupae). The antibacterial properties of Ch-AgNP were proved against Bacillus subtilis, Klebsiella pneumoniae and Salmonella typhi, while no growth inhibition was reported in assays conducted on Proteus vulgaris. Concerning non-target effects, in standard laboratory considtions the predation efficiency of Danio rerio zebrafishes was 68.8% and 61.6% against I and II instar larvae of A. stephensi, respectively. In a Ch-AgNP-contaminated environment, fish predation was boosted to 89.5% and 77.3%, respectively. Quantitative analysis of antioxidant enzymes SOD, CAT and LPO from hepatopancreas of fresh water crabs Paratelphusa hydrodromous exposed for 16 days to a Ch-AgNP-contaminated aquatic environment were conducted. Notably, deleterious effects of Ch-AgNP contaminating aquatic enviroment on the non-target crab P. hydrodromous were observed, particularly when doses higher than 8–10 ppm are tested. Overall, this research highlights the potential of Ch-AGNP for the development of newer control tools against young instar populations of malaria mosquitoes, also highlighting some risks concerned the employ of nanoparticles in aquatic environments.